Improving Students’ Critical Thinking Skills by Reading - Sultonova Maftuna Baxtiyarovna (Researchparks Publishing, 2022)
According to sociologists, our society has now moved to a completely new stage of its development. Today's society is an information society. Constant social development makes more and more new demands on the modern personality. The constantly accelerating rhythm and dynamics of life, huge information flows, various kinds of problems and complex tasks that require immediate solution require the development of new personality traits: personality mobility, creativity, self-management, self-control and self-regulation abilities. In this article described issues based on improving students’ critical thinking skills by reading.